MULTI TIER CROPPING SYSTEM FOR ENHANCING PROFITABILITY IN COTTON - sankaranarayanan, saravanakumar (Indian Farming, 2022)
Multitier cropping systems are dynamic interactive practices aimed at better use of the production components such as soil, water, air space, solar radiation and all other inputs on sustainable basis. Cotton crop is generally cultivated as sole crop in many regions and it is a slow growth nature during the initial stages. Due to improper utilization of interspaces the crops growth has been reduced and increased the crop weed competition ratio. Utilizing the interspaces and duration for maturity, it was advised to go for intercrops and multi tier cropping system in cotton for sustaining their income and improving the soil fertility status. Ever increasing population level, and reduction in cultivable area, forced to adopt recent techniques like inter crops and multi tier crops in cotton for increasing productivity.Â  Highest gross return, net return, per day profitability and weed smothering efficiency were obtained with the multi-tier system of cotton+ radish + coriander.